Utility of "The empowering nurse educators in the changing world" study programme - Elonen, Imane (Czech Republic, 2025)
Nurse educators' competence requirements are constantly evolving. Continuous professional development opportunities vary and there are very few programmes that utilize international collaboration. An Erasmus+ funded New Nurse Educator project developed and implemented a 30 ECTS study programme for nurse educator education and continuous professional development. The aim of the current study is to report the evaluation of the utility of the Empowering Nurse Educators in the Changing World (ENEC) study programme. International descriptive multi method study with a pre-test post-test design was conducted. Evaluation of the impact of the programme on the participants utilized five different instruments and participants' learning diaries. Programme participants were nurse educators and nurse educator candidates from six European countries (n = 42). Analyses indicate that the participants' competence increased in all areas measured after the programme, and that their competence is good. Participants highly valued the international collaboration and exchange of experiences and expertise. The evaluation indicates that international nurse educator education programmes are beneficial for both seasoned and aspiring nurse educators. This study provides novel information on the development and enhancement of nurse educator competence. For further development of continuing professional development, it is crucial to support the development of nurse educator education study programmes in Europe.